UJI BANDING KEKUATAN MUTU BETON PADA ANALISA UJI TEKAN DENGAN MENGGUNAKAN METODE CAPPING SULFUR DAN CAPPING KAPUR - Susilo, Hendro; Paramita, Adhe; Hakim, Teo Lukmanul (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
The compressive strength of concrete is also influenced by the concrete surface itself (capping factor). The capping factor significantly affects the quality values of 15 cm x 30 cm concrete cylinders. In its application, it is expected that we can determine the comparison of concrete compressive strength tests using sulfur capping and lime capping, which is currently uncertain. Therefore, the proof of concrete quality strength with sulfur capping and lime capping for normal concrete with a quality of F'c 25 requires testing the compressive strength values using the UTM Controls machine in the Integrated Laboratory of ITK. The compressive strength testing of concrete quality will be conducted for each sample, consisting of 2 samples each with added sulfur capping and the use of lime capping at the age 14 days, and 28 days. Meanwhile, the mix design for concrete uses the SNI method. The test results show that sulfur capping experiences an increase of 0.19%, while when concrete uses lime capping, there is an increase of 0.7%. Keywords: capping, concrete lime, sulfur